Avaliação de resíduos agrícolas como substrato para produção de hidrolases por fungos filamentosos da Amazônia - Costa, Bianca Kynseng Barbosa da Silva (Brasil, 2020)
Organic waste generated by the food sector has been used as a carbon source for microbial growth and production of hydrolytic enzymes such as cellulases and amylases. The research aimed to test different agricultural residues (Brazil nuts, cassava and banana peels) as substrates for the production of hydrolases by Amazonian filamentous fungi in the municipality of Coari. The fungi were isolated from soil collected at the Medium Solimões Research Support Center by serial dilution followed by plating on Sabouraud Dextrose Agar medium. Agricultural waste from the Coari Municipal Fair was washed, dried and shredded. Enzyme production was obtained by liquid fermentation of the fungi in Manachini medium enriched with the agricultural substrate. Enzyme activity was determined by the Cup-Plate technique and by saccharifying method with 1-3-dinitrosalicylic acid. A total of 63 filamentous fungi were isolated. All selected agricultural residues proved to be viable as an inducing substrate for the production of cellulases and amylases. Among the isolates, 10 were tested in the Cup-Plate, where the fungus AS 36 was the best producer of cellulases in the substrates of chestnut and cassava, with Enzyme Index (I) 5.95 and 5.85 respectively and AS 51 as the best producer of amylases from banana peel obtaining a value of 4.85. As for saccharifying activity, the fungus AS 36 obtained the best performance for amylase and cellulase with 0.81 IU.mL-1, 0.55 IU.mL-1 and 0.48 IU.mL-1 in banana peel substrates chestnut and cassava respectively. The results show the potential for enzymatic production of amylase and cellulase by fungi isolated from Coari soil using regional agricultural residues as inducing substrate.